2020
DOI: 10.1002/ajpa.24141
|View full text |Cite
|
Sign up to set email alerts
|

Male social rank and food competition in a primate multi‐level society

Abstract: Objectives: Social animals often have dominance hierarchies, with high rank conferring preferential access to resources. In primates, competition among males is often assumed to occur predominantly over reproductive opportunities. However, competition for food may occur during food shortages, such as in temperate species during winter. Higher-ranked males may thus gain preferential access to high-profitability food, which would enable them to spend longer engaged in activities other than feeding. Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
(96 reference statements)
0
9
0
Order By: Relevance
“…To meet these energetic needs, dominant animals can exhibit several behavioural and physiological changes that adjust energy intake and expenditure. In many species, dominant animals have priority access to food resources, enabling them to increase energy intake, eat higher quality foods and expend less energy in acquiring food [72,73]. Increasing basal or standard metabolic rates is another change that supports the elevated maintenance costs associated with energetically demanding behaviours.…”
Section: (E) Energy Regulation and Metabolismmentioning
confidence: 99%
“…To meet these energetic needs, dominant animals can exhibit several behavioural and physiological changes that adjust energy intake and expenditure. In many species, dominant animals have priority access to food resources, enabling them to increase energy intake, eat higher quality foods and expend less energy in acquiring food [72,73]. Increasing basal or standard metabolic rates is another change that supports the elevated maintenance costs associated with energetically demanding behaviours.…”
Section: (E) Energy Regulation and Metabolismmentioning
confidence: 99%
“… 28 The dominance rank in most other primate species is individual based, while that in GSMs is OMU based. 33 The rank of an OMU is the likely result of the combined effects of all adult OMU members, 31 , 34 while the dominance rank among females within the same OMU is unclear or inconsistent. 35 We found that OMU rank did not significantly affect response and escape rates ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 42 A cohesive breeding band consists of several OMUs, each of which is made-up of a single adult male, several adult females, and their juvenile and infant offspring that tend to forage and socialize together. 33 The breeding band is shadowed by an all-male band (AMB), which consists of bachelor adult males and sub-adult males excluded from the breeding band. 28 , 43 There is a linear dominance hierarchy among OMUs, 31 reflecting sometimes high competition for food within their groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that males and females use resources with the same energy quality to cover their needs [23] and that males travel further to find food [24], suggesting more energy cost than females. Yet, there are practically no studies focusing on food competition between males (see [25] for an exception), and when males are considered, such analyses do not distinguish between sexes (e.g. [26,27]).…”
Section: Introductionmentioning
confidence: 99%